Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Bisnis Jasa Transportasi Gojek - Andriandita Wijayanto; Riski Dzil Izsisy SP (Yos Soedarso Economic Journal (YEJ), 2022)
This study aims to analyze the effect of service quality on customer satisfaction in the Indonesian GO-JEK transportation service business. This study uses three independent variables, namely tangible, reliability, responsiveness, assurance and empathy with one dependent variable, namely customer satisfaction. After conducting literature and field reviews and preparing hypotheses, the data in this study were collected by distributing questionnaires to 86 people who had used Indonesian GO-JEK transportation as the research sample. The sampling technique used was purposive sampling. The data analysis method used is quantitative analysis, namely validity and reliability tests, classic assumption test, multiple linear regression analysis, t test and F test and the coefficient of determination. Based on data analysis, the results showed that the indicators in this study were valid and reliable. In the classical assumption test the data is normally distributed, there is no heteroscedasticity and multicollinearity. In the tangible, responsiveness, assurance and empathy hypothesis test, they do not have a significant effect on customer satisfaction. And the reliability hypothesis test has a positive and significant effect on customer satisfaction.